Strategies to design extrinsic stimuli-responsive dental polymers capable of autorepairing - Ana P. Fugolin, MS, PhD; Carmem S. Pfeifer, PhD (JADA Foundational Science, 2022)
Objectives. For many years, the requirements for dental polymers were limited to inertially filling the cavity and restoring form, function, and esthetics. Inorganic filler systems were widely enhanced to maximize the mechanical properties and optimize finishing and polishing procedures. The development of alternative photoinitiator systems also improved the carbon-carbon double bond conversion, increasing biocompatibility, wear, and stain resistance. However, despite laudable progress, the clinical life span of dental restorations is still limited, and their replacement is the most common procedure in dental offices worldwide. In the last few years, the development of materials with the potential to adapt to physiological stimuli has emerged as a key step to elevating dental polymers to a higher excellence level. In this context, using polymeric networks with self-healing properties that allow for the control of the propagation of microcracks is an appealing strategy to boost the lifetime of dental restorations. This review aims to report the current state-of-the-art of extrinsic self-healing dental polymers and provide insights to open new avenues for further developments. General classification of the self-healing polymeric systems focusing on the current extrinsic strategies used to inhibit microcracks propagation in dental polymers and recover their structural integrity and toughness are presented. Search Strategy: An electronic search was perfomed using PubMed, Google Scholar, and Scopus databases. Only studies published in English on extrinsic self-healing polymeric systems were included. Overall Conclusions: Self-healing materials are still in their infancy in dentistry, and the future possibilities are almost limitless. Although the mouth is a unique environment and the restorative materials have to survive chemical, physical, and mechanical challenges, which limits the use of some strategies that might compromise their physicochemical performance, there are countless untapped opportunities to overcome the challenges of the current systems and advance the field.